Evaluation of the growth and yield characteristics of various genotypes of the soybean [Glycine max (L.) Merr.] - Singh, Pallavi Kumari; Kushwaha, Ujjawal Kumar Singh; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2022)
Eighteen genotypes of soybean were evaluated in coordinated varietal trial in 2018 and eight genotypes in pre-released varietal trial in 2019 at National Plant Breeding and Genetics Research Centre, Khumaltar, Lalitpur, Nepal. The experimental design was randomized complete block design (RCBD) with three replications. The results showed that the maximum yield was obtained from CN-60 (2858 kg/ha) followed by CM-9133 (2791 kg/ha) in 2018 and CM-9125 (2708 kg/ha) followed by G-1872 (2666 kg/ha) in 2019. Similarly, combined analysis of pre-released varietal trial showed that grain yield was maximum for the LS-22-16-16 (2737.5 kg/ha) followed by G-4508 (2718.5 kg/ha) in 2018 and 2019. Thus, LS-22-16-16 and G-4508 seeds can be delivered to farmers as a farmers acceptance test for the release of soybean variety, while CN-60 and CM-9133 can be promoted to pre-released varietal trial.